MODELING OF DISPENSING COMPONENTS OF MIXTURES IN SOLID BIOFUEL TECHNOLOGIES - Rutylo, М. (Енергетика і автоматика, 2016)
Grounded and developed factual preconditions for the creation of process control dispensing components of mixtures in solid biofuel technologies. A simulation model of intelligent process control systems batching mixtures in the production of solid biofuel and use it to heat generators.pan class="hps">studied their technological equipment. -language:EN-US'>Compensated m - phase (with m = 2k + 1≥3) and single-phase (m = 1) are similar in phase stator windings. Under the scheme rotary autotransformer (AT) from the capacitance at the output were made. The physical processes capacitance induction machines, energy efficiency and special terms of the principle of reversibility were detected.